Expert Design Enterprise / Surinawati Suhaimi ... [et al.] - Suhaimi, Surinawati; Syed Hassan, Sharifah Shahadania; Abd Rahman, Norhayati; Mohd Saad, Haniza; Sulaiman, Fitriyaton; Zakaria, Norhayati (Faculty of Electrical Engineering, 2003)
First thing first, we are glad to introduce our business that have been chosen which is in the Interior Design field. After we had made some discussion, we have agreed to choose 'Expert Design Enterprise' as our business. The type of our business is enterprises since it is easier to handle. Besides, it is also will have a better management through skills, knowledge and experience of each individual partner. The strategic location is being selected through out this area (Shah Alain) that probably considered as one of the best consumer market here. As long as we made the survey here for about one year, we found that Section 9 in Shah Alam is a very strategic location since it is one of the famous market especially to those who want leisure ness and fulfill their self satisfaction.